Community-Based Strategies for the Prevention of Non-Communicable Diseases in Coastal Areas: Meta Analisis - Icmi Ikhtiari Nanjar; Shafinah Binti Ahmad Suhaimi; Ustifina Hasanah Hasibuan; M. Nawawi Lubis; Nisah Nisah (GLOBAL HEALTH SCIENCE GROUP, 2025)
Non-communicable diseases (NCDs), particularly hypertension, represent a major global health burden, especially in vulnerable populations such as coastal communities. Limited healthcare access, combined with socioeconomic and environmental risk factors, contributes to increased hypertension prevalence in these areas. Community-based strategies have been widely promoted as effective approaches to prevention. This study employed a meta-analysis of observational studies following PRISMA guidelines. A systematic search was conducted in PubMed, ScienceDirect, and Google Scholar. Eligible studies included adult populations in coastal areas and reported adjusted odds ratios (aOR) with 95% confidence intervals. Data were analyzed using Review Manager (RevMan), with heterogeneity assessed using the I² statistic and publication bias evaluated through funnel plots. A total of five studies met the inclusion criteria for quantitative synthesis. The findings showed that community-based interventions were significantly associated with reduced hypertension incidence. The adjusted odds ratios ranged from 2.10 to 3.03, indicating a meaningful reduction in risk among exposed populations. The funnel plot demonstrated no substantial publication bias. Community-based strategies are effective in reducing hypertension incidence in coastal populations and represent a scalable approach for NCD prevention.